KARAKTERISTIK RUANG SENI PERTUNJUKAN DI KECAMATAN LEMBANG, BANDUNG BARAT - Djatmiko, Ari; Rohjan, Jajan; Mulyani, Dita; Febriyani, Intan; Alfikri, Salman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The research is motivated by the characteristics of performing arts spaces, both room conditions and supporting facilities. Performing arts as part of the creative industry requires production space and promotional space that supports it, but currently still faces various limited space conditions and a lack of supporting facilities. This research aims to examine the characteristics of performing arts spaces based on the perceptions of performers in Lembang District, West Bandung Regency. This research uses a qualitative approach with exploratory phenomenological methods and narrative analysis. Data was collected through in-depth interviews with artists, bureaucrats and academics. The results of the research show that the characteristics of the production room, according to the perpetrator's perception, show relatively narrow and limited conditions and are combined with the family room. The condition of promotional space is relatively limited, including limited supporting facilities. Apart from that, it was found that the creation of performing arts spaces still has limited support from the government and business actors. Therefore, stronger synergy between stakeholders is needed in creating a performing arts space that is participatory, sustainable and in line with local needs.